Perancangan Sistem Penjualan Online Berbasis Web Untuk Petani Tanaman Bunga Di Desa Cihideung - Jordan Nababan; Henry Pandia (TeIKa, 2017)
One obstacle for flower farmers is how to market the crop products that are produced, and this is the basis of research on designing a web-based sales system for flower plant farmers in Cihideung village. The reason for designing the online sales system is because farmers in the village of Cihideung have not used a system that can assist in the sales process. The purpose of designing an online sales system is to be able to help flower plant farmers in managing sales data to be more effective. The design of this sales system applies the waterfall model, which approaches the design process systematically, which starts at the level of system analysis, design, code, and testing. The results of the system design make it an online sales system that can help flower plant farmers sell their products and increase flexibility for customers who want to shop without having to come to the place. However, the system still has disadvantages, namely not having a security system for online payment transactions, because the payment system is carried out only through transferring bank accounts to buyers and sellers. Therefore, it is recommended that there be further research that can improve the function of the security system for online transaction payment systems, so that it can make it easier for web visitors abroad who want to transact or buy flower plants.